Exendin-4 promotes GSIS without increasing β-cell number through upregulation of glucose-sensing apparatus and mitochondrial oxidative phosphorylation machinery genes in hPSC-derived β-cells - Abdoulaye Diane (14152749) (2023)
Poster by Abdoulaye Diane, Razik Bin Abdul Mu-u-min, Asma Allouch, and Heba H. Al-Siddiqi (Hamad Bin Khalifa University) Background: Impaired insulin secretion contributes to the pathogenesis of diabetes mellitus type 1 (T1DM) through autoimmune destruction of pancreatic β-cells and the pathogenesis of diabetes mellitus type 2 (T2DM) through β-cell dedifferentiation and other mechanisms. Emerging β-cell replacement with human pluripotent stem cell (hPSC)–derived β-cells may provide remedial cell therapy. Most in vitro differentiation protocols have generated hPSC-derived β-cells with either immature phenotype such as impaired or weakened glucose-stimulated insulin secretion (GSIS) relative to primary β-cells. Evidence has shown that β-cell mitochondria play a central role in coupling glucose metabolism to insulin exocytosis. Therefore, the impairment of GSIS in hPSC-derived β-cells may be attributed to impaired glucose sensing and/or mitochondrial dysfunction.  Objective: The aim of this study is to investigate the effect of Exendin-4 (GLP-1 receptor analog), known to promote mitochondrial function, on enhancing maturation and functionality of hPSC-derived β-cells. Methods: Differentiation of hPSC into β-cells was carried out in a stepwise 3D differentiation protocol using 30 ml spinner flask adapted from the protocol of Veres et al. (2019). This consists of 6 stages: S1, definitive endoderm; S2, gut tube endoderm; S3, pancreatic progenitors 1; S4, pancreatic progenitors 2; S5, endocrine precursors; and S6, β-like cells. To determine the differentiation efficiency, relevant stage-specific marker expression was assessed at each stage using flow cytometry. Finally, to further test the effect of GLP-1 receptor analog on the functionality of hPSC-derived β-cells, 50 nM exendin-4 was added to the suspension culture during the last three days of differentiation and GSIS was performed. Gene expression in cell clusters was determined by RT-PCR. Data are mean ± SEM (n=6) Results: Flow cytometry data for relevant stage-specific markers showed 96 % OCT4 positive, 89% SOX17 and 83% PDX1 positive cells, indicating good pluripotency, high definite endoderm and pancreatic progenitor induction, respectively.  As for β-cell markers, we found 41.4% NKX6.1/insulin double positive cells at final stage 6, indicating a generation of β-cells. Expression profiling during differentiation confirmed the generation of insulin-expressing β-cells. However, GSIS data showed no difference in c-peptide secretion between low (2.8mM) and high (20 mM) glucose but high response to direct cellular depolarization-mediated c-peptide by KCl; suggesting a lack of functional β-cells. Interestingly, addition of Exendin-4 (50 nM) during the last 3 days of the differentiation significantly enhanced GSIS associated with increased expression of glucose-sensing apparatus genes (Glut2, G6P2C, GCK) and genes encoding mitochondrial oxidative phosphorylation machinery. Conclusion: Our data demonstrated for the first time in 3D differentiation of hPSC-derived β-cells that addition of Exendin-4 promotes GSIS through upregulation of both glucose-sensing apparatus and mitochondrial oxidative phosphorylation machinery genes without increasing β-cell number.